Evaluating health education module on hand, food, and mouth diseases among preschoolers in Malacca, Malaysia - Shahar, Syazwani; Kadir Shahar, Hayati; Muthiah, Sri Ganesh; K. C. Mani, Kulanthayan (Frontiers Research Foundation, 2022)
This study aims to improve parents' perceptions of susceptibility, severity, benefits, and barriers to children's handwashing practice by utilizing the Health Belief Model. In Alor Gajah, Melaka, a parallel cluster-randomized controlled study was conducted over 26 months. Parents who agreed to participate completed pre-test (t0) questionnaires. Data analysis used IBM SPSS version 25. The descriptive analysis described the baseline data pre-intervention. Chi-square and T-test or Mann-Whitney U test for non-parametric analysis assessed baseline data comparability between intervention and control groups. Generalized Estimating Equation (GEE) analyzed between and within-group comparison of the outcomes, and multivariate analysis determined the effectiveness of the intervention with clustered data. The individual participation rate was 86%. Parents who followed up immediately had higher perceived susceptibility, perceived severity, and perceived barriers (p < 0.001). Each unit increment in parents' practice score was 0.02-unit higher preschool children's hand hygiene practice score (p = 0.045). The intervention effectively improved parents' perceived susceptibility and benefits at immediate follow-up compared to baseline. However, there were no significant intervention effects on parents' perceived severity and barriers and preschool children's handwashing practices. The follow-up time significantly affected each outcome. There were significant covariates as the outcome predictors in this study, besides intervention groups and follow-up time. Parents' knowledge and age of the youngest child were significant predictors of parents' perceived susceptibility, besides parents' knowledge and perceived susceptibility being the predictors of parents' practice score. As a result, parents, teachers, and communities can implement this intervention in other schools with susceptible children.